Analisis Nilai Tambah Pengolahan Kopi Arabika di Doru Coffee Farm Desa Ulian Kabupaten Bangli - Radjendra, A.A Ngurah Ananda; Dewi, Ni Luh Made Indah Murdyani (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
The Arabica coffee industry plays an essential role in enhancing the regional economic value. This study analyzes the added value of Arabica coffee at Doru Coffee Farm using two processing methods, namely honey and full wash, employing the Hayami method. The results indicate that the honey method yields the highest added value for roasted coffee (Rp 28,390.00/kg), followed by green beans (Rp 21,611.25/kg) and ground coffee (Rp 17,791.67/kg), with an added value ratio reflecting viable economic profitability and a unique flavor profile appealing to the specialty market segment. Meanwhile, the full wash method also provides significant added value, with roasted coffee achieving the highest value (Rp 92,316.67/kg), followed by ground coffee (Rp 52,708.33/kg) and green beans (Rp 14,231.67/kg), producing a clean, complex flavor profile with bright acidity suitable for the specialty market. Both methods demonstrate strong potential to enhance the economic value of coffee, with the honey method excelling in product differentiation for the premium market and the full wash method for consistent high-quality output in larger-scale production. The choice of processing method can be tailored to production goals and market preferences.